Analisis Produksi dan Pendapatan Petani Karet di Kabupaten Bungo - Jonni Ali; Arman Delis; Siti Hodijah (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2015)
The purpose of this study was to identify the characteristics of rubber farmers, to determine and analyze revenue and profit rubber production in the sample, to determine and analyze the level of income inequality rubber farmers of the people in the sample, and to identify and analyze the factors that affect smallholder rubber production in the sample. Based on these results suggested to the government should work closely with farmers in encouraging the opening of degraded land through various cooperation for optimal land use, because the land proved to have a significant influence on people's rubber production in Bungo.